Full-Scale Simulation of the Fluid–Particle Interaction Under Magnetic Field Based on IIM–IBM–LBM Coupling Method - Peng, Wei; Hu, Yang; Li, Decai; He, Qiang (Frontiers in Materials, 2022)
In this paper a full-scale computational model for fluid-particle interaction under magnetic field is developed. In this model, the fluid field is solved by the lattice Boltzmann method (LBM) and the hydrodynamics force acting on the particle is computed by the immersed boundary method (IBM). The numerical solutions of magnetic field in the fluid-solid domain are achieved by the immersed interface method (IIM) with a finite difference scheme, in which the normal and tangential jump conditions of the magnetic field intensity are applied to modify the standard finite difference scheme. The magnetic stress tensor along the fluid-particle interface can be calculated accurately. Unlike the widely used point-dipole model, the magnetic force acting on the particle is determined by the stress integration method. Numerical simulation of several numerical tests are carried out to validate the proposed model. The numerical results demonstrate the validity of present model. Moreover, the magnetoviscous effect is studied by simulating the motion of elliptical particle under the uniform magnetic field in shear flow.